Innovation in healthy and functional foods - Ghosh, Dilip K; Ed. Smarta, R B; Ed (CRC Press, 2013)
"Functional food developers are faced with challenges and opportunities in bringing these food products into the marketplace. This book addresses the latest innovation models, the regulatory framework around innovation, and social issues related to consumer perspectives on innovation versus the need for functional food products. Presented by professionals directly involved in the process, chapters cover food safety.